Expert System for Diagnosis of Blood Fever Disease Dengue Using the Chaining and Backward Method Certainty Factor - Rifki Fahrial Zainal; Eko Prasetyo; Achmad Irfan Ferdiansyah (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
Dengue Hemorrhagic Fever is a disease that is quite popular in Indonesia. Judging from the large number of patients infected with the disease and not a small number of patients died due to not being helped immediately. Lack of public sensitivity to the symptoms of dengue hemorrhagic fever is what ultimately causes many casualties,due to late getting medical treatment. Thus, accurate analytical skills are needed in assisting the patient diagnosis process. The Backward Chaining method is a chain that is traversed from a hypothesis back to the facts that support the hypothesis, and the Certainty Factor is a method to prove whether a fact is certain. The system can be run if the user enters the symptoms experienced and provides a confidence value for the symptoms they are experiencing and then gets a diagnosis and a solution.